Antioxidant, Antimicrobial, Anti-Inflammatory, and Gut Microbiota Modulation Effects of Kombucha: a Literature Review - Hananta, Linawati; Kurniawan, Sandy Vitria; Lonah; Arieselia, Zita; Surjono, Edward; Setiawan, Jonny; Lieputra, Andrew Adhytia; Puspa Bunardi, Dewi; Prayoga Tjendratama, Jason; Vallerie Satyadi, Richelle; Dewi, Rita (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2025)
Introduction: The interest in probiotics has increased significantly in recent years. While most probiotic-containing foods are dairy-based, an increasing number of non-dairy probiotic products have emerged, including kombucha. Kombucha is a fermented tea beverage originating from China, known for its high polyphenol content and potential health benefits. Methods: This literature review aims to provide a comprehensive understanding of the health benefits of kombucha. A systematic search of published studies was conducted using the keywords